KONTRIBUSI FILANTROPI INKLUSIF LAZISMU KOTA PROBOLINGGO - Reza Hilmy Luayyin; M. Nabat Ardli; Diana Nuri Nurhidayah (Wasīlah: Journal Of Sharia Sciences, 2025)
This study examines the contribution of inclusive philanthropy implemented by LAZISMU Kota Probolinggo in strengthening socio-economic empowerment within the local community. Using a qualitative descriptive approach, the research explores how LAZISMU integrates the principles of Islamic philanthropy—zakat, infak, and sadaqah—with an inclusive strategy that prioritizes accessibility, equity, and community participation. Data were collected through in-depth interviews, documentation, and direct observation of program activities, followed by thematic analysis to identify patterns of impact and key enabling factors. The findings reveal that LAZISMU Kota Probolinggo has played a significant role in developing programs that reach diverse beneficiary groups, including micro-entrepreneurs, vulnerable families, and students from low-income households. Inclusive practices are reflected in participatory needs assessments, transparent fund management, and integration between religious philanthropy and sustainable development goals. The study also identifies several key factors that strengthen inclusive contribution, such as strong institutional governance, strategic partnerships, community engagement, and a clear orientation toward empowerment rather than charity. Overall, the research concludes that LAZISMU’s inclusive philanthropic model effectively enhances social welfare and promotes economic resilience in Probolinggo. This study contributes to the broader discourse on Islamic social finance by demonstrating how inclusive philanthropy can be operationalized at the local institutional level to achieve impactful and sustainable outcomes. Keywords: LAZISMU, zakat, infaq, sadaqah, fundraising strategy, Sharia-based management, Islamic philanthropy This study aims to analyze the sources of funding managed by the Lembaga Amil Zakat Infaq dan Shodaqah Muhammadiyah (LAZISMU) of Probolinggo City and to examine its fundraising strategies and management mechanisms from the perspective of sustainability and compliance with Islamic principles. The research employs a descriptive qualitative approach using data collection techniques such as interviews, observations, and documentation. The findings reveal that LAZISMU’s sources of funds include zakat, infaq, sadaqah, grants, waqf, corporate social responsibility (CSR), as well as individual and institutional donations. Fund management is carried out in a structured manner through planning, implementation, and evaluation, supported by the Sharia Supervisory Board and the use of digital technology to ensure transparency and accountability. The fundraising strategies involve active donation collection, strategic partnerships, and the optimization of social media platforms. LAZISMU also implements responsive social programs, such as free ambulance services and financial aid for the underprivileged, to enhance public participation and donor trust. Despite challenges such as low zakat literacy and limited human resources, LAZISMU has maintained public trust through professional and Sharia-compliant management. This research is expected to contribute academically to the strengthening of Islamic philanthropic governance and zakat-based community empowerment. Keywords: LAZISMU, zakat, infaq, sadaqah, fundraising strategy, Sharia-based management, Islamic philanthropy